A comparative study of anemia prevalence and associated factors among rural and urban adults in Bangalore, India - Pandurangaiah, Shilpa; Mathew, Annliya Anna; Shettigar, Gowthami (International Journal Of Community Medicine And Public Health, 2026)
Background: Anemia is a major public health concern, particularly among women of reproductive age, and is influenced by socioeconomic, dietary, and health-related factors. This study aimed to compare the prevalence of anemia and associated factors among rural and urban adult populations in Bangalore. Methods: A community-based cross-sectional comparative study was conducted among 300 participants (150 urban and 150 rural residents). Sociodemographic characteristics, dietary practices, anemia awareness, iron supplementation, and hemoglobin levels were assessed using a structured questionnaire and a digital hemoglobinometer. Data were analysed using descriptive statistics and the chi-square test. Results: The overall prevalence of anemia was 29.3%, with significantly higher prevalence among urban participants (42.0%) than rural participants (16.7%) (p<0.001). Urban participants had higher educational attainment (80.0% vs. 2.0%), greater awareness of anemia (51.3% vs. 2.7%), and higher iron supplementation use (25.3% vs. 10.0%) compared to rural participants (all p<0.001). Significant differences were also observed in green leafy vegetable consumption, fruit intake, vitamin C consumption, and healthcare utilization between the two groups. Conclusions: Anemia prevalence differed significantly between urban and rural populations. Despite better awareness and healthcare access among urban participants, anemia burden remained higher, suggesting that complex nutritional, physiological, and lifestyle factors contribute to urban anemia. Targeted, context-specific interventions integrating regular screening, dietary improvement, and supplementation adherence are required.